Mitochondrial genomes from modern horses reveal the major haplogroups that underwent domestication - Achilli, A (2012)
Archaeological and genetic evidence concerning the time and mode of wild horse (Equus ferus) domestication is still debated. High levels of genetic diversity in horse mtDNA have been detected when analyzing the control region; recurrent mutations, however, tend to blur the structure of the phylogenetic tree. Here, we brought the horse mtDNA phylogeny to the highest level of molecular resolution by analyzing 83 mitochondrial genomes from modern horses across Asia, Europe, the Middle East, and the Americas. Our data reveal 18 major haplogroups (A-R) with radiation times that are mostly confined to the Neolithic and later periods and place the root of the phylogeny corresponding to the Ancestral Mare Mitogenome at ~130-160 thousand years ago. All haplogroups were detected in modern horses from Asia, but F was only found in E. przewalskii--the only remaining wild horse. Therefore, a wide range of matrilineal lineages from the extinct E. ferus underwent domestication in the Eurasian steppes during the Eneolithic period and were transmitted to modern E. caballus breeds. Importantly, now that the major horse haplogroups have been defined, each with diagnostic mutational motifs (in both the coding and control regions), these haplotypes could be easily used to (i) classify well-preserved ancient remains, (ii) (re)assess the haplogroup variation of modern breeds, including Thoroughbreds, and (iii) evaluate the possible role of mtDNA backgrounds in racehorse performance.